Kombinasi Program Motor Lesson, Roprioceptive Neuromuscular Facility Dan Latihan Core Stability Terhadap Peningkatan Keseimbangan Duduk Untuk Berdiri Dan Postural Kekuatan Otot Penderita Stroke - Sri Saadiyah Leksonowati; Sudaryanto Sudaryanto (Jurnal Health Sains, 2022)
ABSTRACT The global stroke epidemiology is changing rapidly. Although age-standardized stroke death rates have declined worldwide in the last two decades, the absolute number of people who have a stroke each year, live with the consequences of stroke, and die from stroke are increasing. This study aims to determine the effect of a combination of motor relearning programs, proprioceptive neuromuscular facilitation and core stability exercise on improving sitting-to-standing balance and postural muscle strength in stroke patients. This research is a pre-experimental study involving treatment variables, namely a combination of motor relearning programs, proprioceptive neuromuscular facilitation and core stability exercise, while the response variables are sitting to standing balance and postural muscle strength in stroke patients. The target population was stroke patients at the hospital in Makassar City, while the sample for this study was 45 stroke patients at the Makassar City Hospital at the time of the study. This study used the Berg Balance Scale, and Manual Muscle Testing for Sitting to Standing Balance and Muscle Strength before and after the intervention with a frequency of 1 time a week for 3 months. The results of the MRP, PNF and Core Stability studies, the mean balance of the pretest value is 0.64 ± 0.484 (scale 0-4), and the post test value is 3.04 ± 0.767 (scale 0-4), and the p value is 0.000 or < 0.05, the mean pretest value of muscle strength is 0.64 ± 0.484 (0-5 scale), and the post test value is 3.42 ± 0.583 (0-5 scale), and the p value is 0.000 or <0.05. In conclusion, the combination of motor relearning programs, proprioceptive neuromuscular facilitation and core stability exercise has an effect on increasing sitting to standing balance and postural muscle strength in stroke sufferers.